The mediating role of amotivation on teachers' workload perception, stress appraisal, and coping - Geronimo, Floren B.; Olegario, Lizamarie C.; Oael, Irene C.; Pedrajita, Jose Q. (Quezon City College of Education, University of the Philippines Diliman, 2020)
This study aimed to identify teachers' workload perception, stress appraisal, and its relationship with each other. It also sought to determine teachers' motivation in terms of teaching and non-teaching-related tasks, and the role of motivation to teacher' workload perception and stress appraisal. Moreover, it identified the coping strategies teachers' used in dealing with work overload in their workplace. This study used a Sequential Explanatory Design which consisted of quantitative and qualitative phases. 345 teachers were surveyed in the quantitative phase and 18 participants were selected for the focus group discussion which served as the qualitative phase of this study. The study showed that teachers' workload was divided into teaching-related tasks and non-teaching-related tasks. It was found out that task outside their teaching duties are causing them the most stress. Teachers' workload perception was found to have a significant correlation to stress appraisal and they used different coping strategies to address the stressful situation of work overload. It was also identified that teachers were manifesting different types of motivation both in doing teaching and non-teaching-related tasks. However, amotivation, a non-self-determined form of behavior, is revealed to predict majority of the dependent variables in this study. Amotivation was seen as an antecedent to teachers' negative beliefs and perceived negative consequences in their work. It also preceded and predicted the behavior they manifested toward their work which influenced different facets of their perception and stress appraisal. These findings only showed that teachers' motivation was not exclusive to intrinsic and extrinsic motivation but it also extended to amotivation, a construct that is often underplayed in trying to understand teachers' behavior at work.
Thesis
Keywords: Teachers -- Workload -- Philippines -- Manila Metropolitan Area; Teachers -- Job stress -- Philippines -- Manila Metropolitan Area; Stress management -- Philippines -- Manila Metropolitan Area; Teachers -- Attitudes -- Philippines -- Manila Metropolitan Area